Empagliflozin in patients with autosomal dominant polycystic kidney disease (EMPA-PKD): study protocol for a randomised controlled trial - Roland Schmitt; Sebastian Häckl; Armin Koch; Elisabeth Bahlmann-Kroll; Stefanie Kramer; Vera Christine Wulfmeyer; Julian Glandorf; Jessica Kaufeld; Dagmar Hartung; Bernhard M W Schmidt; Kai Schmidt-Ott (BMJ Open)
Introduction Autosomal dominant polycystic kidney disease (ADPKD) is a hereditary condition that causes the formation of cysts primarily in the kidneys. The continuous growth of multiple cysts leads to the destruction of functional parenchyma, which may progress to end-stage kidney disease. Tolvaptan is the only drug specifically approved for slowing down the progression of ADPKD. Sodium-glucose transporter 2 inhibitors might provide additional benefits but there is currently no information on safety and outcome effects of SGLT2i in patients with ADPKD, as these patients were excluded in SGLT2i trials. In particular, there has been speculation that SGLT2i might increase cyst growth and accelerate the loss of kidney function in ADPKD. The EMPA-PKD trial is assessing the safety of empagliflozin in patients with rapid progressive ADPKD with and without concomitant tolvaptan use by monitoring the total kidney volume and the loss of kidney function.Methods and analysis This is an investigator-initiated, double-blind, single-centre, placebo-controlled, randomised clinical trial including patients with rapidly progressive ADPKD (n=44). Participants will be randomly allocated (1:1) to receive a daily dose of either empagliflozin (10 mg/day) or placebo for 18 months. Patients will be stratified according to concomitant tolvaptan use. The primary endpoint is the progression of cystic kidney growth by monitoring MRI-based changes in total kidney volume and the secondary endpoint is the change in glomerular filtration rate. Additional endpoints include changes in copeptin levels, albuminuria and blood pressure.Ethics and dissemination The protocol has been approved by the German Federal Institute for Drugs and Medical Devices (BfArM) after review by the independent ethics committee Landesarztekammer Rheinland-Pfalz. Participation in this study will be voluntary and informed consent will be obtained. Regardless of the outcome, the results will be disseminated through a peer-reviewed international medical journal.Trial registration numbers EU-CT number 2023-505890-34-00, NCT06391450.